Effect of Valsartan on Renal Marker, Nitrite and Histopathology of Kidney in Ischemia/Reperfusion Induced Renal Damage in Diabetic Rats - Nehal Shah, Jagdish Kakadiya*, (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Present study was designed to evaluate the effect of Valsartan on renal marker, nitrite and histopathology of kidney in Ischemia/reperfusion induced renal damage in diabetic rats. Ischemia/reperfusion injury, which is commonly seen in the field of renal surgery or transplantation in diabetic condition, is a major cause of acute renal failure. Type 2 Diabetes was induced in rats by a single intraperitoneal (i.p) injection of Streptozotocin (65 mg/kg, STZ) in overnight fasting rats followed by the i.p administration of Nicotinamide (110 mg/kg, NIC) after 15 minutes. After right nephrectomy, Valsartan (8 mg/kg/day, p.o) was administered for 15 days. On the 16th day, ischemia was induced in contra lateral kidney for 45 min, followed by reperfusion for 24 hr. Renal function marker and histopathology were estimated at the end of 24 hr reperfusion. At the end of experimental period the level of nitrite in kidney tissue, serum marker Albumin and Blood urea nitrogen were significantly changed. Valsartan improved the renal dysfunction and nitrite after renal ischemia/reperfusion injury in diabetic rats. Light microscopic evaluation of the kidneys of the diabetic rats with I/R only showed tubular cell swelling, interstitial edema, tubular dilatation, and moderate to severe necrosis, whereas, Valsartan improve tubular dilation, loss of interstitial hemorrhage, and glomerular atrophy. In conclusion, Valsartan as a beneficial agent on renal marker, nitrite and histopathology of kidney in Ischemia/reperfusion induced renal damage in diabetic rats. ——————————————————————- Pharmacology Department, Dharmaj Degree Pharmacy College, Petlad-Khambhat Road, Dharmaj, Anand-388430, Gujarat, India *Corresponding author, Email: jagdishkakadiya@yahoo.co.in, Tel: +919825882522 Â Cite This Article As: Jagdish Kakadiya, Nehal Shah. 2010. Effect of Valsartan on Renal Marker, Nitrite and Histopathology of Kidney in Ischemia/Reperfusion Induced Renal Damage in Diabetic Rats. J. Ecobiotechnol. 2(3): 12-17.